Faktor-Faktor yang Mempengaruhi Implementasi SAK EMKM pada UMKM Kota Padang - Dewi Wulandari; Fefri Indra Arza (Universitas Negeri Padang, 2022)
This study aims to determine the factors that influence the implementation of SAK EMKM on UMKM in the city of Padang. The data used in this study are primary data sourced from questionnaires given to the owners of UMKM in the city of Padang. Testing is done by using regression. The results showed that simultaneously the independent variables consisting of socialization of SAK EMKM, utilization of information technology, accounting knowledge, education level of the owner, omzet and length of business did not significantly affect the dependent variable, namely the implementation of SAK EMKM. Partially, the socialization of SAK EMKM and the owner's level of education have a positive effect on the implementation of SAK EMKM. While the use of information technology, accounting knowledge, omzet and length of business have no significant effect on the implementation of SAK EMKM in Padang City.